Assessment of Apoptosis in Women Using Oral Contraceptives - Shalish, Worood K.; Nada, Saad M.; Yahya, Abdalgani I. (Iraqi Journal of Science, 2018)
The aim of the study was the examination of the effect of birth control pills (Yasmin) on women who utilized the pills by measuring the percentage of apoptosis. The investigation was based mainly on the calculation of the apoptosis percentage of blood lymphocytes in women who used the pills for different durations. The results of the presented study was obtained from 25 women handling birth control pills and 15 women who had not used pills. According to the period of contraceptive pills treatment, the samples were classified into two categories: (2-5) years and (6-8) years. Results showed that the percentage of apoptosis in pills handling women (2-5) years were (7.08%) while the results were (12.2%) in women who used birth control pills (6-8) years. In addition, the results values were significantly different (P≤0.05) from those in control, which were (0.18%). Based on the results obtained in this study, it is concluded from that the percentage of apoptosis increase with the prolonged use of Yasmin.